Comparative analysis of a specific type of lexical collocation (light verb + noun) in Croatian, Italian and English language and its use in classroom teaching of lexis - Alujević, Marijana (Array, 2020)
The aim of this paper is to provide an overview and the analysis of collocations, one of the most significant aspects of idiomatic use of language. A special emphasis has been put on a comparative review of the most common Light Verb Constructions consisting of light verbs (cro. lagani glagoli, ital. verbi supporto) and nouns in Croatian, English and Italian language. The aforementioned construction is chosen since it is extremely common in the early stages of language acquisition. Moreover, the aim of the conducted contrastive analysis has been to determine overlaps in order to use the examples of positive transfer in teaching lexis (English/Italian – L2), as well as to prevent negative interference such as false analogies. The research is based on the assumption that the number of completely concordant collocations taught in the early stages of foreign language acquisition is limited. Thus, prompt detection and putting emphasis on their relevance is essential. Following the discussion of the results of the contrastive analysis, the relevance of teaching collocations, i.e. presenting the most common collocations simultaneously with new vocabulary will be stressed. In accordance with the abovementioned, we believe that collocational approach is the most useful and effective in teaching languages.